PERSPEKTIF MORALITAS DALAM PERKARA ABORSI - Stanislaus Atalim (Jurnal Yudisial, 2011)
ABSTRACTAbortion remains one of social, legal, and moral issues most hotly debated. Each perspective presents powerful pro-con arguments. The pro-life and moral arguments emphasize on preserving human life or giving absolute priority to the life of the unborn fetus and even over the life of the mother. However, pro-social choice group argues that a woman should have a right to control her body includes her pregnancy. In Indonesia, abortion is legally permitted at any rate with some exceptions. In judging abortion cases, the court or panel of judges must take account of moral reasoning as the other side of his argument and must not limit only accordance with legal reasoning. This article presents the other side of legal argument, that is moral argument which can be regarded as lex generalis, while legal argument as lex specialis. Hence, there is a mutual connection between legality and morality especially in abortion cases.Keywords: abortion, legal reasoning, moral reasoning ABSTRAKAbsorsi menjadi salah satu perdebatan hangat dengan isu moral yang berdimensi sosial dan hukum, dimana setiap pandangan memiliki argumen yang berbeda satu dengan yang lain. Bagi kaum pendukung moral dan kehidupan memiliki argumen untuk memberikan kehidupan secara mutlak bagi bayi sama halnya dengan sang ibu. Sementara, kaum sosial berargumen bahwa perempuan memiliki hak untuk mengkontrol tubuhnya termasuk kehamilannya. Di Indonesia, aborsi secara hukum dilarang dengan beberapa pengecualian. Dalam kasus putusan aborsi, hakim seharusnya tidak hanya mengunakan argument hukum saja. Dalam tulisan ini memperlihatkan sisi di luar aspek hukum seperti aspek moral dianggap lex generalis, seemntara aspek hukum sebagai lex specialis. Oleh sebab itu, di sana terdapat mutual connection antara aspek hukum dan moral dalam kasus aborsi.Kata kunci: aborsi, alasan hukum, alasan moral